2010
DOI: 10.1590/s0101-60832010000600002
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades psicométricas de um protocolo neuropsicológico breve para uso em populações geriátricas

Abstract: Background: The increase in life expectancy and proportion of elderly in the population is causing an increase in dementia prevalence rates. The correct, early diagnosis of dementia is very important to clinical treatment and to improved prognosis. Therefore, it is necessary to adapt and develop assessment tools for the differential diagnosis between pathological and normal aging processes. Objective: Assess the psychometric properties and the factorial structure of a neuropsychological protocol used in geriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
0
9
0
6
Order By: Relevance
“…These measures were selected for representing different aspects of cognition (general and specific), involving language, memory, visuospatial skills, attention and executive functions, as recommended in previous studies (Salmon and Bondi, 2009; Weintraub et al, 2009). All aforementioned measures have been cross-culturally adapted and validated for use on the Brazilian population (de Paula et al, 2010, 2013a). …”
Section: Methodsmentioning
confidence: 99%
“…These measures were selected for representing different aspects of cognition (general and specific), involving language, memory, visuospatial skills, attention and executive functions, as recommended in previous studies (Salmon and Bondi, 2009; Weintraub et al, 2009). All aforementioned measures have been cross-culturally adapted and validated for use on the Brazilian population (de Paula et al, 2010, 2013a). …”
Section: Methodsmentioning
confidence: 99%
“…Most Brazilian studies on VF include SVF tasks using the animal category (Araujo et al, 2011;Brucki, Malheiros, Okamoto, & Bertolucci, 1997;Brucki & Rocha, 2004;Caramelli, Carthery-Goulart, Porto, CharchatFichman, & Nitrini, 2007;Lopes et al, 2009;Silva, Yassuda, Guimarães, & Florindo, 2011). There is a small number of studies using fruits (Paula et al, 2010), body parts (Malloy-Diniz et al, 2007), and clothes (Fonseca, Parente, Côté, Ska, & Joanette, 2008;Moraes et al, 2014;Zimmermann, Parente, Joanette, & Fonseca, 2014). PVF tasks are also mentioned in national studies using the letters F, A, and S (Charchat-Fichman et al, 2011;Fonseca, Salles, & Parente, 2009;Machado et al, 2009), the letter P (Fonseca et al, 2008;Moraes et al, 2014;Zimmermann et al, 2014), and the letter M (Charchat-Fichman et al, 2011;Salles et al, in press).…”
mentioning
confidence: 99%
“…Several studies have suggested that tests of executive functions may be more influenced by education 28,52,53,54 . Caramelli et al 5 demonstrated that the Verbal Fluency animal category, a traditional measure of executive function, had a high accuracy for AD, as long as education adjusted cut-off scores were used.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that visuospatial tasks involving drawings are particularly difficult for older adults with little or no formal education 52,53,54 . Other studies have underlined the need for caution when interpreting Clock Drawing Test findings, as the level of education is a potential source of bias 46,56 .…”
Section: Discussionmentioning
confidence: 99%